Analisis Kebutuhan Buku Ajar Bahasa Inggris Matematika Berbasis Collaborative Learning untuk Mahasiswa Pendidikan Matematika - Deswita, Hera; Niati, Batdal (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2020)
Books are teaching materials that are designed as learning resources arranged systematically so that students can use them to achieve learning goals. Teachers and lecturers must have the ability to develop teaching materials according to the needs of their students. The purpose of this study was to describe the needs of mathematics students for Collaborative Learning-based mathematics English textbooks. This research method is descriptive qualitative. The research subjects were 21 students of Mathematics Education, Pasir Pengaraian University who had completed English courses. Data collected through questionnaires and interviews with indicators: (1) the ease of students in learning English (2) the need for students to master English in the face of the ASEAN Economic Community (AEC) era, (3) the student's need for learning English mathematics resources, (4) the student's need for textbooks involving students to actively read, write, and discuss (5) the student's need for an attractive, easy-to-carry and economical appearance of English mathematics textbooks (6) student interest in Collaborative Learning-based textbooks. The results showed that students needed an English mathematics textbook based on Collaborative Learning